Dengue Fever in a One Health Perspective - Aparecida Sperança, Márcia (Infectious Diseases, 2020)
Dengue Fever in a One Health Perspective underlines important aspects of dengue virus, the most prevalent and life-threatening arbovirus in the world. Over three sections, chapters cover such topics as biological and environmental aspects, physiopathology, molecular biology, diagnosis, and control strategies. The first section provides knowledge on basic aspects of dengue virus biology and its emergence and re-emergence associated to environmental changes. The second section includes two chapters on dengue immunopathology, a drawback in disease control and vaccine development. Finally, the third section examines molecular biology tools employed in dengue virus immunopathogenesis studies, diagnosis, drug design, and in the use of vectors as sentinels in surveillance and vector biology studies.